Twenty-five years of natural products research in NuBBE - Mannochio-Russo, Helena; Pires dos Santos, Ana Letícia; Bueno, Paula Carolina Pires; Vieira, Rafael; Ferreira Pinto, Meri Emili; Silva Queiroz, Suzana Aparecida; Dutra, Luiz Antonio; Gaspareto Felippe, Lidiane; Nastri de Luca Batista, Andrea; de Souza-Moreira, Tatiana Maria; Valli, Marilia; Previate Medina, Rebeca; et al. (Frontiers in Natural Products, 2023)
The richness of Brazilian biodiversity translates into a valuable collection of molecules with biological properties that range from ecological functions to pharmacological properties. For over 25 years, the Nucleus of Bioassays, Biosynthesis, and Ecophysiology of Natural Products (NuBBE) has conducted extensive investigations into the chemical entities of numerous plant and microorganism species, resulting in the discovery of over a thousand natural compounds spanning various chemical classes (such as shikimate derivatives, phenylpropanoids, terpenoids, alkaloids, and peptides). The research goals within the natural products field encompass phytochemical studies, investigations of endophytic fungi and marine organisms, biosynthetic studies, medicinal chemistry, and the development of innovative methodologies. This comprehensive review article aims to offer valuable insights into the multifaceted research endeavors conducted in NuBBE. In this way, accomplishments, perspectives, and opportunities for advancing natural products research in Brazil are highlighted, seeking to inspire and motivate other research groups in the field of natural products–especially those located in emerging countries with rich biodiversity.